Perception and preference of caregivers towards routine immunization amidst COVID-19 - A., Ragavi; Mannu, Alexander; Vasudevan, Jaishree; Chellaiyan D., Vinoth Gnana (International Journal of Contemporary Pediatrics, 2022)
Background: Immunization rates for routine vaccines show a drop during the COVID-19 pandemic. To assess the perception and preferences of caregivers towards routine immunization services amidst COVID-19. Methods: A cross-sectional study was conducted in southern Chennai and adjoining districts of Chengalpattu and Kanchipuram, Tamil Nadu. The duration of the study was from January to June 2021. Parents of under-five children residing in the community for the last 3 years were selected as the study population. Using a simple random technique, 431 participants were selected. A pilot study was conducted with 50 participants to check for the comprehension and validity of the questionnaire and subsequent changes have been done. The co Guide version V.1.0.3 was used for statistical analysis. Results: The majority 236 (54.76%) of the study population were residents of the urban locality. Two hundred (46.40%) participants were women attending antenatal clinics. A majority (395, 91.65%) felt their child needs all recommended vaccines according to national immunization schedule. If vaccines were missed, the major reason was (168, 38.98%) lockdown. Conclusions: The present study population was well aware of routine immunization. Imposition of lockdown caused a disturbance in scheduled vaccinations and there was hesitancy of caregivers for COVID-19 vaccine to their children.